Evaluating the long‐term persistence of Bacillus spores on common surfaces. Issue 6 (3rd May 2018) - Enger, Kyle S.; Mitchell, Jade; Murali, Bharathi; Birdsell, Dawn N.; Keim, Paul; Gurian, Patrick L.; Wagner, David M.
Summary: Bacillus spores resist inactivation, but the extent of their persistence on common surfaces is unclear. This work addresses knowledge gaps regarding biothreat agents in the environment to reduce uncertainty in risk assessment models. Studies were conducted to investigate the long‐term inactivation of Bacillus anthracis and three commonly used surrogate organisms – B. cereus, B. atrophaeus and B. thuringiensis on three materials: laminate countertop, stainless steel and polystyrene Petri dishes. Viable spores were measured at 1, 30, 90, 196, 304 and 1038 days. Twelve different persistence models were fit to the data using maximum likelihood estimation and compared. The study found that (1) spore inactivation was not log‐linear, as commonly modelled; (2) B. thuringiensis counts increased at 24 h on all materials, followed by a subsequent decline; (3) several experiments showed evidence of a 'U' shape, with spore counts apparently decreasing and then increasing between 1 and 304 days; (4) spores on polystyrene showed little inactivation; and (5) the maximum inactivation of 56% was observed for B. atrophaeus spores on steel at 196 days. Over the range of surfaces, time durations and conditions (humidity controlled vs. uncontrolled) examined, B. thuringiensis most closely matched the behaviour of B. anthracis . Abstract : This work is the first of its kind to jointly present an experimental and modelling study that characterizes the long‐term persistence of Bacillus spores on common surfaces by natural decay over a 3 year period. The implications of model selection and extrapolation beyond the final time point are elucidated for microorganisms that persist for long periods of time on environmental media. The study also informs the selection of suitable surrogates based on their behaviour under similar conditions over time.